Retrospective analysis of difficulties during mastoid surgeries in tertiary referral center in Nepal - Neupane, Yogesh; Kharel, Bijaya; Dongol, Kripa; Pradhananga, Rabindra B.; Rayamajhi, Pabina; Dutta, Heempali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Complications can occur during and following mastoidectomy because of the variation in the temporal bone anatomy and surgical factors. The operating surgeon needs to be aware of potential difficulties and their clinical relevance to avoid the dread complication. This study aims to study various per-operative difficulties and complications encountered during mastoid surgery. Methods: A retrospective study was conducted, including 152 cases of chronic otitis media squamous type who underwent mastoidectomy from June 2017 to January 2019. Revision cases and cases with missing records on per-operative findings, early postoperative status, hearing assessment were excluded from the study. Results: Out of 152 cases, there were 80 males and 72 females with a mean of 27.5 years. Dural plate breach was recognized in 19 cases (12.5%) with iatrogenic injury in 16 cases. Breach of sinus plate and exposure of sigmoid sinus was noted in 11 cases (7.24%) and all were iatrogenic. Korner’s septum was noted in five cases (3.29%). The facial canal was dehiscence in 25 cases (16.4%) with the majority in the horizontal segment, but the sheath was intact in all cases. Immediate postoperative facial nerve palsy was seen in four cases (2.6%). Fistula in the lateral semi-circular canal was noted in two cases. Taste disturbance was noted in 13 cases. Local complications related to the surgical site was seen in 19 cases. Conclusions: The anatomic variations and surgical difficulty are common in mastoid surgery. The major complication rate is around 2-3% despite various mastoid variation and difficulties.